The National Technology Mapping Programme Phase ll, 6 June 2001, Putra World Trade Centre, Kuala Lumpur - Industrial Workshop on Analysis of Value Chain, Product and Technology (Machinery Industry) (2001 : Kuala Lumpur) ([s.l. : s.n.], 2001)
36